PENGARUH PROPORSI KEPEMILIKAN PUBLIK DAN TRANSPARANSI KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN - Danka Winata, Ardiansyah R (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to gain empiricist validation in regards to the effect of public ownership proportion and financial transparency to the quality of financial report. Samples in this report include 328 general public who are aware of Public Listed Kimia Farma LTD and provided with information about the display form of the company’s financial report which listed in the Indonesia Stock Exchange or Bursa Efek Indonesia (BEI). Data in this report is treated with the SPSS 25. The result of this report shows that the public ownership proportion and financial transparency have a significant impact on the quality of the financial report. It is believed that adding new independent variables to enhance the overall independent variables in explaining the dependent variables could improve the financial report.